A Study on User Experience of Automotive HUD Systems: Contexts of Information Use and User-Perceived Design Improvement Points. Issue 20 (14th December 2019) - Beck, Donghyun; Jung, Jaemoon; Park, Juhee; Park, Woojin
ABSTRACT: Despite three decades of use and related research efforts, how automotive HUD can be designed to best serve the driver is still an on-going research issue. For any human-machine system, studying the experiences of the existing users is an important first step towards design improvement and innovation. Nonetheless, surprisingly few studies have investigated the user experience of the existing commercial automotive HUD systems. In an effort to address the research gap, the current study conducted a user survey on the usage contexts and design improvement points of the existing automotive HUD systems focusing on eleven high-priority HUD information items selected among those displayed by the existing commercial HUD systems. A total of fifty-one drivers with significant prior HUD use experience participated. Design implications were derived from the survey responses. They may be useful for improving the existing automotive HUD systems in both the system functions and the interface/interaction design.